Konstruksi Maskulinitas dalam Film Seperti Dendam, Rindu Harus Dibayar Tuntas - Fathiyah Nurshabrina Rahmah; Dyah Ayu Wiwid Sintowoko; Teddy Ageng Maulana (Institut Seni Indonesia Yogyakarta, 2025)
Construction of Masculinity in The Movie Vengeance Is Mine, All Others Pay Cash.This study examines the construction of masculinity in the 2021 film “Seperti Dendam, Rindu Harus Dibayar Tuntas” (Vengeance Is Mine, All Others Pay Cash), focusing on the use of cinematographic and mise-en-scene elements to represent fragile masculinity. The film follows Ajo Kawir, a man grappling with childhood trauma that disrupts his sense of masculinity, particularly in terms of sexuality and emotion. This research employs a descriptive qualitative method by analyzing eight selected scenes that reflect aspects of masculinity. The theoretical framework includes cinematography, mise-en-scene, and masculinity theories such as hegemonic masculinity and toxic masculinity. The findings reveal that the film portrays masculinity not only through physical strength but also through vulnerability, especially in confronting sexual crises and emotional conflict. The use of color, lighting, framing, and costume enhances the masculine identity and inner turmoil of the characters. Moreover, the film presents an unconventional gender dynamic, particularly through the character Iteung, who displays strength and dominance, thereby reshaping the power relations between men and women. This analysis offers new insights into the construction of masculinity in Indonesian cinema, emphasizing the role of visual elements in shaping social meaning and masculine identity.